Religiosity and investment knowledge as determinants of cryptocurrency investment interest among Muslim Generation Z - M. Farhan Zubaili; Azimah Dianah; Rina Desiana; Nor 'Adha Ab Hamid (Indonesian Journal of Islamic Economics Research, 2026)
The phenomenon of digital asset investment development, particularly cryptocurrency, has garnered significant attention among young Generation Z investors. However, limited studies have examined the respective roles of religiosity and investment knowledge in shaping cryptocurrency investment intention within a Muslim-majority context, especially in regions implementing Islamic values such as Aceh, Indonesia. This study aims to analyze the influence of religiosity and investment knowledge on cryptocurrency investment intention among Muslim Generation Z. The research employed a quantitative approach, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The results indicate that religiosity has a negative and significant effect on investment intention, while investment knowledge has a positive and significant effect. These findings suggest that individuals with a high level of religiosity tend to avoid cryptocurrency investments due to legal uncertainty and Islamic perspectives concerning elements of gharar (uncertainty), maysir (speculation), and dharar (harm). Conversely, a higher level of investment knowledge enhances individuals' ability to make rational and ethical financial decisions. This study contributes theoretically by extending the Theory of Planned Behavior into the context of Islamic digital finance, highlighting religiosity as a normative constraint and investment knowledge as a cognitive driver in shaping cryptocurrency investment intention among Muslim Generation Z.